2020
DOI: 10.1038/s41598-020-74664-y
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Sox10 is an essential determinant of branching morphogenesis and involution in the mouse mammary gland

Abstract: The high mobility group-domain containing transcription factor Sox10 is an essential regulator of developmental processes and homeostasis in the neural crest, several neural crest-derived lineages and myelinating glia. Recent studies have also implicated Sox10 as an important factor in mammary stem and precursor cells. Here we employ a series of mouse mutants with constitutive and conditional Sox10 deficiencies to show that Sox10 has multiple functions in the developing mammary gland. While there is no indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It is first expressed in embryonic neural crest stem cells (NCSCs), where its self-reinforcing gene regulatory module facilitates multipotency and cell migration, orchestrating the embryo patterning process 25 28 . Once patterning is complete, SOX10 is silenced in all NCSC descendants except glial and melanocyte progenitors; and is nascently induced in ectoderm-derived epithelial progenitor cells of the salivary, lacrimal, and mammary glands 29 33 . In the mouse, Sox10 is an obligate requirement for mammary gland development.…”
Section: Introductionmentioning
confidence: 99%
“…It is first expressed in embryonic neural crest stem cells (NCSCs), where its self-reinforcing gene regulatory module facilitates multipotency and cell migration, orchestrating the embryo patterning process 25 28 . Once patterning is complete, SOX10 is silenced in all NCSC descendants except glial and melanocyte progenitors; and is nascently induced in ectoderm-derived epithelial progenitor cells of the salivary, lacrimal, and mammary glands 29 33 . In the mouse, Sox10 is an obligate requirement for mammary gland development.…”
Section: Introductionmentioning
confidence: 99%
“…When carcinomas are involved, these stem-like cells are usually specified as cancer stem cells (CSCs) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Since members of the SOX protein family serve as versatile regulators of stem- and progenitor-cell fates [ 131 , 132 , 133 , 134 , 135 ], we next investigated the expression patterns of SOX2, SOX9, and SOX10 transcription factors in WM115 (primary) and WM266-4 (metastatic) melanoma cells via an immunofluorescence protocol employment ( Figure 4 ). SOX2 proved to be highly accumulated in all WM115 cell nuclei, while its detection could hardly be recognized in WM266-4 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that miR-424/503 targets genes such as IGF1R and BCL2 in the mammary epithelium and that its loss affects developmental processes (involution) and tumorigenesis (Llobet-Navas et al, 2014a;Rodriguez-Barrueco et al, 2017;Mertelmeyer et al, 2020). The newly discovered regulation of WNT signaling presents a clearer and more complete view of the function of this microRNA cluster modulating mammary epithelial fate.…”
Section: Regulation Of Mammary Epithelial Dynamics By Mir-424(322)/503mentioning
confidence: 91%